Desempenho agronômico de abobrinha italiana em função do espaçamento entre plantas - Cordeiro, Carlos Jardel Xavier (2016)
Planting densities is a very important tool for planters, considering that, according to consuming market demands, we may handle it in order to obtain better financial return and increasing production. The aim of this work was to evaluate the agronomic performance of zucchini (courgette) cultivars under different planting spacing. The experiment was accomplished in Experimental Farm Rafael Fernandes, belonging to Universidade Federal Rural do Semi-Árido (UFERSA), in Mossoró-RN. The experimental design was in complete randomized blocks in factorial scheme 2 x 4 with four repetitions. The treatments were formed by the combination of two zucchini (courgette) cultivars (Alice and Caserta) and four repetitions among plants (0.40 m; 0.50 m; 0.60 m e 0.70 m). The following quality characteristics were evaluated: number of marketable fruits per plant, total number of fruits per plant, market production per plant, total production per plant, market productivity, total productivity, number of non-commercial fruit per plant; non-commercial production per plant, mass of marketable fruit, mass of non-commercial fruit, non-commercial productivity, plant dry mass, soluble solids, titratable acidity and relation soluble solids/ titratable acidity. The cultivars reacted differently to the spacing among plants, in such a way distances 0.7 and 0.4 allowed the highest market productivity, respectively, for Alice and Caserta. The distances did not influence the quality of zucchini (courgette) fruit